Practical Aspects Of Using Modern Technologies In Music Education - Mamadolimova Malikaxon Mamatisak's Qizi (Peerian Journals Publishing, 2024)
This article discusses the effective use of modern technologies in music education today and the impact of creating new educational literature that fully meets educational standards on the quality of education.
Keywords: Perfect generation; national values; Multimedia; Internet